Cathepsin C Is Involved in Macrophage M1 Polarization via p38/MAPK Pathway in Sudden Cardiac Death - Jialin Dai; Jiangjin Liu; Qiong Zhang; Yang An; Bing Xia; Changwu Wan; Yuanyuan Zhang; Yanni Yu; Jie Wang (Cardiovascular Therapeutics)
This study was aimed at identifying molecular markers associated with the pathogenesis of sudden cardiac death (SCD). It provides a proteomic analysis of human left anterior descending coronary artery from subjects diagnosed with SCD through histological examination and cases of nondisease accidental deaths through autopsy. A total of 2784 proteins were obtained from label-free quantitative proteomic analysis. This included a total of 265 differential proteins which were involved in SCD-related processes, such as inflammation, muscle system process regulation, metal ion transport, and lysosomal pathway. Western blotting was carried out to measure the expressions of cathepsin C (CTSC), focal adhesion kinase (FAK), p-FAK, and proteins related to the p38/MAPK signaling pathway, whereas immunohistochemistry was performed to determine the localization and expression of CTSC, TNF-α, and CD206 in arterial tissues. It was found that CTSC were the most expressed proteins with a significant upward trend in SCD cases. Besides, CTSC regulated macrophage polarization to M1 through the FAK-induced p38/MAPK signaling pathway. This promoted the release of inflammatory factors and eventually increased the inflammatory response. In conclusion, this study implies that CTSC may be one of the key molecular targets for promoting macrophage M1 polarization in SCD, which may provide new therapeutic insights into the treatment of inflammatory diseases.